Kebutuhan perawatan berpusat keluarga dalam manajemen diabetes pada anak dengan diabetes melitus - Sri Hendrawati; Ikeu Nurhidayah; Fanny Adistie (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Diabetes mellitus (DM) is a serious disease that has the potential to cause complications and affect all ages, including children. Diabetes care management is needed to maintain blood glucose levels at an adequate level. Children, especially at an early age, have an inability to carry out various tasks related to proper diabetes care management. Family centered care is one strategy to empower families in diabetes care management to prevent complications. The purpose of this study was to identify the needs of parents in the management of diabetes care in children with DM type 1. This study was conducted in one hospital in Bandung. The type of research used is descriptive quantitative. This study used a total sampling technique to obtain 25 parents with children with DM. Data was collected using a Diabetic Care Needs Assessment Tool with 23 questions that were seen through the difficulty level of parents in meeting those needs. Data were analyzed using frequency distribution and percentage. The results obtained data on family centered care needs in the management of diabetes in children ranging from the most difficult to be fulfilled to those that were not difficult to fulfill in terms of the proportion of parents who stated it was information and education needs (32%), emotional needs (24%), collaboration and collaboration needs (20%), and psychosocial needs (8%). The most difficult thing for more than half the parents of children with diabetes mellitus is the information and education needs. Nurses can help parents to meet the management needs of diabetes care in children, especially information and education that parents need. Education that can be provided by nurses, including regular insulin administration, regular blood glucose control, physical exercise activities, appropriate menus, and self-management or self-care in children to improve the quality of life in children with diabetes.